Maturity related differences in body composition assessed by classic and specific bioimpedance vector analysis among male elite youth soccer players - Toselli, S.; Marini, E.; Latessa, P. M.; Benedetti, L. (International Journal of Environmental Research and Public Health, 2020)
The aim of this study was to analyze the e ciency of classic and specific bioelectrical impedance vector analysis (BIVA) in the assessment of maturity related di erences in body composition among male elite youth soccer players, and to provide bioelectrical impedance reference data for this category. A group of 178 players (aged 12.1 1.6 years) were registered in a professional Italian soccer team participating in the first division (Serie A). They were divided into three groups according to their maturity status while bioelectrical resistance and reactance were obtained. The classic and specific BIVA procedures were applied, which correct bioelectrical values for body height and body geometry, respectively. Percentage of fat mass (FM%) and total body water (TBW (L)) were estimated from bioelectrical values. Age-specific z-scores of the predicted age at peak height velocity identified 29 players as earlier-, 126 as on time-, and 23 as later-maturing. TBW was higher (p < 0.01) in adolescents classified as "early" maturity status compared to the other two groups and classic BIVA confirmed these results. Conversely, no di erences in FM% were found among the groups. Specific vector length showed a higher correlation (r = 0.748) with FM% compared with the classic approach (r = 0.493). Classic vector length showed a stronger association (r = ..0.955) with TBW compared with specific (r = ..0.263). Specific BIVA turns out to be accurate for the analysis of FM% in athletes, while classic BIVA shows to be a valid approach to evaluate TBW. An original data set of bioelectric impedance reference values of male elite youth soccer players was provided.